2017
DOI: 10.1002/hipo.22766
|View full text |Cite
|
Sign up to set email alerts
|

Memory integration in humans with hippocampal lesions

Abstract: Adaptive behavior frequently depends on inference from past experience. Recent studies suggest that the underlying process of integrating related memories may depend on interaction between hippocampus and prefrontal cortex. Here, we investigated how hippocampal damage affects memory integration. Subjects with mediotemporal lesions and healthy controls learned a set of overlapping AB- and BC-associations (object-face- and face-object pairs) and were then tested for memory of these associations ("direct" trials)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 37 publications
6
33
0
Order By: Relevance
“…Our findings provide evidence that MTL structures, including the hippocampus, are essential to enabling the rapid integration of new information within stored knowledge in a schematic structure. These results align well with previous studies that revealed the critical role of the hippocampus in enabling inferential learning between different episodic events that overlap in the perceptual content in healthy individuals (Schlichting and Preston 2015;; and in patients with lesions in the MTL (Pajkert et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings provide evidence that MTL structures, including the hippocampus, are essential to enabling the rapid integration of new information within stored knowledge in a schematic structure. These results align well with previous studies that revealed the critical role of the hippocampus in enabling inferential learning between different episodic events that overlap in the perceptual content in healthy individuals (Schlichting and Preston 2015;; and in patients with lesions in the MTL (Pajkert et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The formation of the integrative representation can be achieved either at encoding of BC (termed integrative encoding), or at retrieval (termed retrieval inference; [2]). As shown in Pajkert et al [14], across cycle, healthy middle-age participants showed an increasing reliance on integratively encoded representations for AC-decisions. That is, with repeated necessity of AC-decisions, participants might have increasingly tended to form integrated ABC-representations when encoding the BC-pairs (by reactivating the corresponding AB-pair).…”
Section: Introductionmentioning
confidence: 77%
“…In the current study, we compared children, adolescents, and young adults on their ability to form memory integration across overlapping associations. We examined memory inference using a modified version of the associative inference task [14]. Here, participants also learned a set of overlapping AB- (object-face) and BC- (face-object) associations and were then directly tested on memory of these associations (“direct” trials) and on inferential AC-associations (“inference” trials).…”
Section: Introductionmentioning
confidence: 99%
“…In this division of labor, the hippocampus is thought to encode details of unfolding events and reactivate details of past events, while the mPFC is thought to find commonalities across episodes and bias hippocampal reactivation towards relevant past events (Preston & Eichenbaum, 2013). In line with these predictions, patients with lesions to either the mPFC (Spalding et al, 2018) or the hippocampus (Pajkert et al, 2017) suffer deficits in the memory integration that cannot be explained by deficits in associative memory alone. As the nature of these lesions did not change between encoding and inference, however, these studies do not clarify whether these regions specifically impair integrative encoding.…”
Section: Episodic Memories Are Integrated Across Event Boundariesmentioning
confidence: 91%